87.9k views
2 votes
Help guys this was from a while back so i don’t remember

Help guys this was from a while back so i don’t remember-example-1

1 Answer

5 votes

Answer: x = 3

Step-by-step explanation: both expressions are equal to each other because the angles are opposite of each other, so you would set the expressions equal to each other and solve from there.

set equations = to each other: 6x - 7 = 4x - 1

add 7 to the other side: 6x = 4x + 6
subtract 4x to the other side: 2x = 6

divide both sides by 2: x = 3

User Barry Chum
by
5.0k points